Book Review: Traveller, Nomadic and Migrant Education - Colin Clark (Journal of Research in Rural Education, 2010)
It is the measure of a persuasive, convincing and thought-provoking book when, after turning the last page, you find that you are left with a lot more questions to ponder than those that have been answered for you in the preceding text. For example, what initiatives and policies can best facilitate the integration and education of mobile populations? Does the provision of an appropriate and suitable education demand the settlement of such nomadic populations, at least for a certain period of time? Is there a useful distinction to be made between the cultural traditions and norms that fuel movement, as opposed to "mere" economic and commercial necessity? What geographies and populations work "best" in providing messages and lessons to which other countries and groups can aspire, both in a literal and metaphorical sense? And, above all else, does education " for mobile populations and other such groups " have to take place in schools and other public/state institutions or can education now be delivered, thanks largely to advancing Information and Communications Technology (ITC), via a number of imaginative and innovative methods that allows for nomadism and education to cohabit and stop being regarded as somehow mutually exclusive? Thoughts, arguments, opinion on all of the above rage on, of course, but Traveller, Nomadic and Migrant Education makes a bold and ambitious contribution to the debates and acts as a fascinating example of the advantages and drawbacks of aiming "big" and sharing experiences from a range of geographies and communities under the banner of a single edited text book.